Is There Any Relation between Serum Levels of Interleukin-10 and Neurophysiological Abnormalities in Bell’s Palsy? - Maghbooli, Mehdi; Esmaeilzadeh , Abdolreza; Karami Zarandi, Fatemeh; Jafarzadeh , Arezoo; Biglari , Sajjad; Azizi Shalbaf , Nazanin; Farhoudi , Negar (Acta medica Lituanica, 2021)
Background: Bell’s palsy is the most common cause of peripheral facial palsy. The etiology and treatment of Bell’s palsy are still controversial. Previous studies emphasize the role of herpes simplex and herpes zoster viruses in this ailment. The role of Interleukin-10 (IL-10) in Bell’s palsy is yet unknown, and few studies have shed light on the matter. This study intended to assess the prognostic value of IL-10 and its relation to the intensity of electrodiagnostic abnormalities and evaluate its potential use as a factor for judging the need for medical or surgical interventions. Materials and Methods: 30 patients in the acute phase of Bell’s palsy participated in this study. Peripheral blood samples were obtained for IL-10 assessment within the first 72 hours (before commencing treatment), and a nerve conduction study (NCS) was performed six days after symptom onset. Results: There was no significant correlation between IL-10 serum levels and the severity of nerve conduction pathology in Orbicularis oculi and Orbicularis oris muscles. Also, IL-10 serum levels did not show any meaningful relationships with participants’ age, gender, or symptoms. Conclusion: The IL-10 serum levels are not relevant to the pathology of Bell’s palsy, and the assessment of IL-10 serum levels cannot be used as an alternative to NCS for evaluating the severity of acute Bell’s palsy.